Albania’s Parliamentary Election of 2009 – Dependence from Permanent Change of Election System - Çeka, Blendi (Richtmann Publishing, 2012)
The experiment with the new election system created some anomalies which are reflected to the entire model of democracyAlbania is applying. The election final result resembles more to a majoritarian product than a proportional one. The new election systemalso produced ideologically questionable fragile majority and a very strong opposition in terms of number of mandates in the parliament.Permanent institutional crisis, lack of mutual trust and understanding between the main political parties, dysfunctional parliament, andfailure to reach the candidate status as the next step to EU membership are key indicators of the impacts that the new election systemhad on entire political system. Due to that, there are a lot of initiatives coming from different actors aiming the modification of the actualelection system in order to increase the proportional nature of it. The political discourse in Albania is coming back to the starting pointwhere new modifications of the election system are required in order to minimize the negative impacts of the actual one, without takinginto consideration the country profile. In case there are modifications, the main parties remain the key designers of them, which meantheir immediate interests are fully respected. The question is what is considered a good election system for Albania? As long as thequestion is not correctly addressed the best change political actors can do to the election system is for the first time after twenty yearsnot changing it.